Implementation methods and applications of flow visualization in a watershed simulation platform. (October 2017) - Zhang, Shanghong; Li, Wenda; Lei, Xiaohui; Ding, Xiaowen; Zhang, Tianxiang
Highlights: We studied flow visualization techniques in a virtual watershed simulation platform. End users can conveniently explore modeling results within a virtual 3D environment. Integrated display and comprehensive analysis of flow data were implemented. Efficient rendering of large watershed flow is possible with the presented methods. Platform application can enhance flow visualization in water resources management. Abstract: Computer-based flow visualization, which is an important approach to examine both the dynamic flow process and to elucidate the laws of fluid movement, can greatly facilitate our understanding of the complicated hydrologic cycle and provide insights into regional water resources management. Nevertheless, at present, few software tools can efficiently perform different flow visualizations for watershed modeling. In this study, a virtual watershed platform was developed and various implementation methods of flow visualization were assessed, such as scalar field visualization, vector field visualization, and visual water effects. In the platform, spatially distributed flow model results and georeferenced datasets are visualized in a virtual 3D environment. End users can conveniently explore modeling results within that environment. Based on analysis of the varying requirements of the flow visualization methods applied to watershed simulation, overheads associated with a user-determined switch between different systems were reduced, and the level of comprehensive information management and analysis of large volumes of watershed data was improved. This study shows that application of the watershed platform can enhance flow visualization in the water resources research community, and makes related water modeling more practical in support of water resources management.